A novel strategy for the application of levulinic acid with simultaneous NAD+ regeneration and membrane separation of products. Issue 6 (December 2022) - Bachosz, Karolina; Smułek, Wojciech; Zdarta, Jakub; Jesionowski, Teofil
Abstract: In this study, we present the concept of co-immobilization of 3-hydroxybutyrate dehydrogenase with xylose dehydrogenase or glucose dehydrogenase on the XN45 nanofiltration membrane for application in the bioconversion of levulinic acid as well as xylose or glucose with simultaneous cofactor regeneration. During the research, changes in the properties of the membrane were defined before and after the co-immobilization of enzymes and the effectiveness of this process was confirmed. Using produced multifunctional systems, the efficiencies of 4-hydroxyvaleric acid, xylonic acid or gluconic acid production were over 98 %. The highest yields of acids production were obtained for systems with substrate ratio 1:1, enzyme ratio 1:1 and cofactor ratio 1:1, irrespectively of the enzyme used. Additionally, the co-immobilization of enzymes made it possible to carry out ten successive catalytic cycles and storage of the biocatalyst for 10 days without a significant decrease in the efficiencies of the processes, all acids were synthetized with over 50 % of productivity. The presented results confirm the effective protein co-immobilization, improvement of their stability and the possibility of their reuse, as well as the effective cofactor regeneration. Therefore the developed two enzymatic systems might be promising in application in the conversion of biomass components. Graphical Abstract: ga1 Highlights: Multienzymatic systems were co-immobilized on nanofiltration membrane efficiently. Levulinic acid, xylose or glucose bioconversion were performed with 98 % efficiency. Effective cofactor regeneration has been achieved for the system with XN45 membrane. The obtained results proved the simultaneous bioconversion and product separation. High stability and reusability characterized the co-immobilized systems.